2008
DOI: 10.1038/npp.2008.16
|View full text |Cite
|
Sign up to set email alerts
|

Ethanol Regulation of D1 Dopamine Receptor Signaling is Mediated by Protein Kinase C in an Isozyme-Specific Manner

Abstract: Ethanol consumption potentiates dopaminergic signaling that is partially mediated by the D 1 dopamine receptor; however, the mechanism(s) underlying ethanol-dependent modulation of D 1 signaling is unclear. We now show that ethanol treatment of D 1 receptor-expressing cells decreases D 1 receptor phosphorylation and concurrently potentiates dopamine-stimulated cAMP accumulation. Protein kinase C (PKC) inhibitors mimic the effects of ethanol on D 1 receptor phosphorylation and dopamine-stimulated cAMP levels in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
50
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(53 citation statements)
references
References 51 publications
0
50
1
Order By: Relevance
“…Moreover, we found that EtOH decreases constitutive PKC phosphorylation of the D 1 receptor with a concomitant potentiation of dopaminergic signaling (Rex et al, 2008). It is noteworthy that EtOH was found to directly inhibit the enzymatic activities of PKC␥ and PKC␦, but only when they were isolated from the plasma membrane fraction, an effect that was not observed for other PKC isozymes that were tested (Rex et al, 2008). The molecular mechanisms underlying the EtOH-mediated inhibition of membrane-associated PKC␥ and PKC␦ kinase activities and how they target the D 1 receptor are at present unclear.…”
mentioning
confidence: 82%
See 3 more Smart Citations
“…Moreover, we found that EtOH decreases constitutive PKC phosphorylation of the D 1 receptor with a concomitant potentiation of dopaminergic signaling (Rex et al, 2008). It is noteworthy that EtOH was found to directly inhibit the enzymatic activities of PKC␥ and PKC␦, but only when they were isolated from the plasma membrane fraction, an effect that was not observed for other PKC isozymes that were tested (Rex et al, 2008). The molecular mechanisms underlying the EtOH-mediated inhibition of membrane-associated PKC␥ and PKC␦ kinase activities and how they target the D 1 receptor are at present unclear.…”
mentioning
confidence: 82%
“…We determined recently that PKC constitutively phosphorylates the D 1 receptor and that this negatively regulates dopaminergic signaling (Rex et al, 2008). Moreover, we found that EtOH decreases constitutive PKC phosphorylation of the D 1 receptor with a concomitant potentiation of dopaminergic signaling (Rex et al, 2008). It is noteworthy that EtOH was found to directly inhibit the enzymatic activities of PKC␥ and PKC␦, but only when they were isolated from the plasma membrane fraction, an effect that was not observed for other PKC isozymes that were tested (Rex et al, 2008).…”
mentioning
confidence: 86%
See 2 more Smart Citations
“…PKA can phosphorylate T268 in the third intracellular loop and T380 in the carboxyl terminus of D1R, which regulates either the rate of desensitization or intracellular trafficking of the receptor once internalized (Jiang and Sibley, 1999;Mason et al, 2002). Constitutive or heterologous PKC (including PKCa, bI, g, d, and e) phosphorylates D1R and dampens DA activation of the receptor, thus attenuating D1R-mediated signaling (Gardner et al, 2001;Rankin and Sibley, 2010;Rex et al, 2008;Rex et al, 2010). Here we provided both in vitro and in vivo evidence for the involvement of PKD1 in D1R phosphorylation.…”
Section: Discussionmentioning
confidence: 99%